Reward Strategy, Employee Development Towards Employee Retention Through Job Satisfaction as an Intervening Variable and SOPs as a Mediation Variable in Line with SDGs No.10 to Reduce Inequality - Supardi, Supardi; Sriyono, Sriyono; Muhammad Ashar, Muhammad Ashar (International Journal of Artificial Intelligence Research, 2025)
It examined the relationship between objective rewards and development methodologies and employee retention, mediation of job satisfaction, and mediation by standard operating procedures (SOP). This study specifically relates to Sustainable Development Goal (SDG) No. 10, which seeks to reduce inequality whereby just and fair retention practices create an environment inclusive and fair work. The methodology for this research was quantitative - surveys were used as the main instrument for the collection of data. The data were collected from 92 respondents at the Asam-Asam PLTU in Tanah Laut Regency, South Kalimantan. Path analysis was used for testing the formulated hypotheses. Performance appraisal results revealed that employee rewards and development methodologies influence job satisfaction and employee retention. Job satisfaction is a major encroaching variable because higher job satisfaction increases the likelihood that employees will stay in the organization. Furthermore, the implementation of transparent and equitable SOPs mediated the relationship between management strategies and employee retention, thereby ensuring that organizational practices were coherent and minimizing disparities among employees. These results imply that effective employee retention depends not only on financial incentives but also on perceptions of fairness and equal opportunity, which are facilitated by robust SOP. In summary, it recommends that for the organizations to attain higher employee retention rates, they'll have to measure accordance with SDG 10 by instituting systematic reward and development strategies under transparent SOPs, targeted at comprehensive job satisfaction improvement.